Developing a Therapeutic Protocol: Integrating Progressive Muscle Relaxation and Hypnotic Suggestion Based on Lao Tzu’s Principles for Anxiety Disorders - Semwal, Ashish; Juyal, Tripti (Journal of Neonatal Surgery, 2025)
Feeling anxious is a big deal for many people around the globe. It can seriously get in the way of enjoying life and functioning well, which means we constantly need to find new, whole-person, and individual-focused ways to help. This paper introduces the idea and basic design for a new therapy approach called the Tao-PMR-Hypnosis (TPH) protocol. It’s all about easing the complex symptoms of anxiety by blending a few powerful techniques: the body-calming benefits of Progressive Muscle Relaxation (PMR), the mind-reshaping abilities of clinical hypnosis using specific suggestions, and the guiding wisdom of Lao Tzu's ancient book, the Tao Te Ching. Key ideas from Taoism that shape this TPH protocol include "wu wei" (like effortless action or letting things unfold naturally), the strength found in being gentle and flexible ("rou"), the peace that comes from simplicity ("pu"), and the overall goal of living in harmony with nature's way (the Tao). First, this paper takes a look at anxiety itself—what it feels like, where it comes from, and some of the downsides or difficulties with current common treatments like medication or standard talk therapies. Then, it dives into some key Taoist ideas and how they can help us understand and change the experience of anxiety. After that, we’ll explore PMR and clinical hypnosis as therapies, looking at their history, how they work, what’s usually involved, and how effective they are for anxiety and stress. The main part of this paper explains the proposed TPH protocol in detail: its core ideas, how it would be structured in phases, the specific techniques used in each phase, and ideas for how sessions could look in a clinical setting. This approach aims to see anxiety not just as a bunch of symptoms to get rid of, but as a deeper sign that our mind, body, and spirit are out of balance. The TPH protocol suggests that we can gently but powerfully restore this balance by learning to find deep inner calm, become more mentally flexible, release physical tension while becoming more aware of our bodies, and live more consciously in tune with universal principles of natural balance, effortless living, and self-kindness. We’ll use some fictional examples to show how it might work, and then talk honestly about the potential benefits, possible drawbacks, and important ethical things to keep in mind. Finally, we’ll suggest what kind of research is needed to really test and improve the TPH protocol. By creatively mixing timeless wisdom with proven modern techniques, the TPH protocol hopes to offer a kind, respectful, and deeply healing path for reducing anxiety and helping people live fuller, more peaceful lives